The performing arts in medieval Islam : shadow play and popular poetry in Ibn Daniyal's Mamluk Cairo - Guo, Li, 1956- (Islamic History and Civilization, 2012)
This is a study of the life and work of Ibn Dāniyāl (d. 1310), a Cairo-based eye doctor, poet, playwright, court jester, and arguably one of the most controversial cultural figures of his time. Drawing on medieval Arabic sources, many still in manuscript and some used for the first time, the author further contextualizes Ibn Dāniyāl's work with respect to poetry production and popular culture in the Islamic Near East in the post-Mongol period. The book also presents the first full English translation of "The Phantom," one of Ibn Dāniyāl's three shadow plays, the only surviving pre-Ottoman Arabic theatrical texts.